#10yearschallenge could simplify data collection, expert says - Zulhuda, Sonny (The Jakarta Post, 2019)
he #10yearschallenge has recently swept across social media, with users posting pictures of themselves in 2009 and 2019. It is argued that the hashtag could be a shortcut used for data collection. Speaking to Antara news agency in Kuala Lumpur, Sonny said netizens mostly participated in the challenge for entertainment and nostalgia purposes. However, he also said users might not realize the photos could be used for other purposes that could help social media companies or third parties in their lines of work. These include improving databases of users’ faces based on age, time period, race, gender and environment.